STRUKTUR BETON BERTULANG DALAM PERSPEKTIF FLEKSIBILITAS BENTUK DAN ARSITEKTUR PLASTIS PADA RANCANGAN DEKONSTRUKSI - Pujantara, Ruly (Universitas Negeri Makassar, 2014)
Since the Time of Architecture Renaissance, when the concrete was first time to be used as a structure and shaping a faÃ§ade of the building, until this time of post modern era the concrete was still became a first choices to be used because its strength, its plasticity and its flexibility to support the architectural design, especially in shaping and forming the building design. The concrete technology nowadays with additional advance material in combination, makes the quality of the concrete became more developed to support face of architecture with form and shape. Perspective of the art of concrete in architectural plasticity is the main theme to discuss more comprehensive in this journal, based on review of Architecture Deconstruction.Â Keywords: concrete structures, concrete technology, architecture deconstruction